Upaya pencegahan penyebaranan Covid- 19 melibatkan peran kader/rt/rw di kabupaten bekasi tahun 2020 - Mila Sartika (Lentera Negeri, 2021)
COVID-19 is currently a global problem, categorized as a global pandemic. One of the prevention steps is to comply with the health procedures, involving the participation of cadres in the community. Cadre is a person or group of people who are fostered by a management agency in an organization. The purpose of PKM is to minimize the risk of spreading COVID-19 in the community. The PKM method provides education "preventing the spread of Covid-19 with 7M and Isoman". Evaluation uses an observation sheet. Implementation of PKM on February 12, 2021 in Hall Rw.12, Mangunjaya Village, South Tambun District, Bekasi Regency. The target of cadres/RT/RW is 51 respondents. PKM output; Posters and Pocket Books that have been copyrighted. The results of the first stage of PKM; reduce mobility by 19.69%, 18.80% of residents wear masks, while washing hands, maintaining distance, applying coughing and sneezing etiquette, avoiding stress and isoman is still low below 10%. The second stage of evaluation increased above 11%, and the third stage of evaluation increased public awareness with the results of residents washing their hands with soap 84.66%, wearing masks 83.14%, avoiding stress 56.19%, avoiding crowds 52.62% , reduce mobility 51.68%, keep a distance 51.26%, apply cough and sneeze etiquette 45.79% and Isoman 1.62%. The global pandemic problem can seize people's worries so that it can worsen the condition if a solution is not immediately found. One of the most appropriate solutions in dealing with this global pandemic is through education.